(untitled) (Altre Modernità, 2013)
In this issue I intend to study how the Argentine writer Leopoldo marechal (1900-1970) re-elaborates the motif of Revelation in his novel Adán Buenosayres (1948) as well as in two discarded autograph and unpublished pages of the final manuscript. I will review the sketch that Marechal writes, and finally reject, of the legend of the fire theft carried out by a Caracara, among the tobas Indians, as intertext which postulates a creolization of the Promethean story. Will also analyse another two approaches of the Apocalypse in the aforementioned novel: the collapse of the amatory pretensions of the protagonist and the generational Apocalipse, through the interpretation of the death of Adán Buenosayres as a retrospective and critical balance of the ultraista-martinfierrista experience.